STRENGTHENING THE RESILIENCE OF MSME CERAMIC CRAFT GUWANG VILLAGE THROUGH DIGITAL MARKETING STRATEGY - Rustanti, Ni Made Diah Karisma; Kalfika Anggria Wardani, Kadek Devi; Putu Adhiya Putri, Dewa Ayu (LPPM Univ. Ibn Khaldun Bogor, 2022)
Guwang Village is known for its handicrafts, one of many handicrafts is ceramic crafts. The occurrence of the Covid-19 pandemic and marketing strategies that are still conventional has led to a decline in the industrial sector making it increasingly difficult for people who have a business to sell their products, causing income by the business owner to decrease. The application of digital marketing strategies through social media can be the main choice for SME owners to do marketing. Lack of knowledge about digital marketing makes the products offered still not well known by the public. The solution that will be given is to development of knowledge and digital marketing assistance by utilizing social media as a forum for doing digital marketing. The method used is Participatory Rural Appraisal (PRA). The purpose of this activity is that the author wants to help SMEs in Guwang Village ceramics to strengthen MSME resilience through the application and assistance of digital marketing strategies. The activities that have been carried out have been able to increase the ability of ceramic handicraft MSME using digital marketing. By utilizing digital marketing as a medium for marketing, the product can be better known by many people and bigger to expand the market